Cognitive radio platforms: a survey. - Martínez Marrero, Liz; Urquiza Villalonga, David Alejandro; Hernández Inguanzo, Eddy; Torres Gómez, Jorge (Telemática, 2016)
The increasing demand of mobile users imposes a better utilization of the available spectrum. In this regard, Cognitive Radio (CR) technology represents a novel solution for avoiding spectrum scarcity. The implementation of the CR system follows two different approaches: Mitola Radio, which takes control of all parameters, and Cognitive Radio with just Spectrum Sensing (SS) techniques. This paper will be concerned with SS techniques. From a theoretical point of view, CR is addressed through several solutions in regard to novel SS methods. However, system and hardware development is progressing at a lower pace. Today, field-programmable gate arrays (FPGAs) and regular desktop computers are fast enough to handle complete baseband processing chains. There are several platforms, both open source and commercial, providing such solutions for supporting the development of novel SS methods. The aims of this paper is to give an overview of some of the available platforms and testbeds and their characteristics, and compare the features and performance measures of the different systems.